2010
DOI: 10.4049/jimmunol.1000927
|View full text |Cite
|
Sign up to set email alerts
|

CD137-Mediated Pathogenesis from Chronic Hepatitis to Hepatocellular Carcinoma in Hepatitis B Virus-Transgenic Mice

Abstract: Chronic hepatitis B virus (HBV) infection is characterized by sustained liver inflammation with an influx of lymphocytes, which contributes to the development of cirrhosis and hepatocellular carcinoma. The mechanisms underlying this immune-mediated hepatic pathogenesis remain ill defined. We report in this article that repetitive infusion of anti-CD137 agonist mAb in HBV-transgenic mice closely mimics this process by sequentially inducing hepatitis, fibrosis, cirrhosis, and, ultimately, liver cancer. CD137 mAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 31 publications
3
75
0
Order By: Relevance
“…Very few investigations have evaluated how memory CD8 ϩ T cells affect fibrosis development in infectious models. Previous studies have suggested that fibrosis associated with chronic hepatitis is promoted by nonspecific activation of memory CD8 ϩ T cells (28,40). For a bleomycin-induced fibrosis model, it was hypothesized that recently activated memory T cells may contribute to lung pathology via interaction with inflammatory dendritic cells (DCs) (1).…”
Section: Discussionmentioning
confidence: 99%
“…Very few investigations have evaluated how memory CD8 ϩ T cells affect fibrosis development in infectious models. Previous studies have suggested that fibrosis associated with chronic hepatitis is promoted by nonspecific activation of memory CD8 ϩ T cells (28,40). For a bleomycin-induced fibrosis model, it was hypothesized that recently activated memory T cells may contribute to lung pathology via interaction with inflammatory dendritic cells (DCs) (1).…”
Section: Discussionmentioning
confidence: 99%
“…As studies revealed that immune mediated necro-inflammation is another cause of HCC development [151]. It was found that CD8 + T cell causes hepatic inflammation derive by INF gamma [152]. It was demonstrated that metabolic syndrome (MS) was associated with both cryptogenic cirrhosis and nonalcoholic steatohepatitis, Currently MS can be consider as an independent and major risk factor for CHB infection related Cirrhosis [153155] and HCC development [156].…”
Section: Oxidative Stress Induced Hcc By Hbvmentioning
confidence: 99%
“…T cells in the livers can be used as the standard of damage for livers [23]; in this experiment, we detected the level of CD4+ cells and CD8+ cells by means of the flow cytometry detection. Comparing the two groups of mice, we could find that in 16 h after the injection of Concanavalin A, the concentration of the CD4+ and CD8+ in HBV transgenic mice livers is higher than that in the normal mice's livers, which told us that the HBV transgenic mice were more facile to be damaged by the stimulation than the normal mice in immunology.…”
Section: Discussionmentioning
confidence: 99%